Influence of mixed-surfactant on reductive dechlorination of trichloroethylene by zero-valent iron - Shin, Min-Chul; Yang, Jung-Seok; Park, Geun-Yong; Baek, Kitae (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2011)
Mixed nonionic and cationic surfactants were used to enhance the reductive dechlorination rate of trichloroethylene (TCE) with zero valent iron (ZVI). Among tested combinations of four cationic and three nonionic surfactants, a mixed surfactant system of hexadecyl-trimethyl ammonium (CTAB) and Brij30 at a mixing ratio of 1: 1 with 0.5 critical micelle concentration (CMC) exhibited the highest reaction rate constant, 0.0269 h(-1); the dechlorination rate constant of TCE with ZVI in the absence of surfactant was 0.0206 h(-1). effect of this mixed surfactant on the reductive dechlorination of ICE was investigated using ZVI in a column to simulate field conditions. Unlike batch tests, column tests of the mixed surfactant system exhibited higher and lower TCE removal as compared to a nonionic and a cationic surfactant system, respectively. Consequently, if surfactants are applied for surfactant-enhanced aquifer remediation (SEAR), the performance of a permeable reactive barrier (PRB) system using ZVI to remove the residual ICE in groundwater might be affected by surfactant types; thus, the application should be carefully considered.
Keywords: PERMEABLE REACTIVE BARRIER; NONIONIC SURFACTANT; INORGANIC CONTAMINANTS; CATIONIC SURFACTANTS; DEGRADATION; GROUNDWATER; REMEDIATION; TOXICITY; KINETICS; TETRACHLOROETHYLENE